Literature Review: Application of Artificial Intelligence in Higher Education Business Education to Improve Students’ Computational Thinking - Rahma, Adelia; Setyawati, Amelia; Ibadil Maula, Farij; Trisnawati, Novi; Putri Mega Pratesa, Dimas (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
The phenomenon of technology integration in higher education is growing, with Artificial Intelligence (AI) being the main highlight in supporting the teaching and learning process. This research aims to develop a strategy for implementing AI in business education in higher education to improve students' computational thinking skills. The novelty of this research lies in the innovative approach that combines AI with interactive teaching methods and data analysis for learning personalization. The urgency of this research is driven by the pressing need for a computational thinking workforce in the digital era. The method used in this research is Systematic Literature Review (SLR) by collecting relevant previous research through publish or perish then analyzing the articles and narrowing them down with keywords. The results showed that the effective use of AI can improve students' analytical and problem-solving skills. The implications of these findings include policy recommendations for universities to adopt AI as an educational tool, which is expected to better prepare students for the challenges of Industry 4.0.